2016
DOI: 10.3390/s16122025
|View full text |Cite
|
Sign up to set email alerts
|

Short-Range Vital Signs Sensing Based on EEMD and CWT Using IR-UWB Radar

Abstract: The radar sensor described realizes healthcare monitoring capable of detecting subject chest-wall movement caused by cardiopulmonary activities and wirelessly estimating the respiration and heartbeat rates of the subject without attaching any devices to the body. Conventional single-tone Doppler radar can only capture Doppler signatures because of a lack of bandwidth information with noncontact sensors. In contrast, we take full advantage of impulse radio ultra-wideband (IR-UWB) radar to achieve low power cons… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(44 citation statements)
references
References 38 publications
0
40
0
Order By: Relevance
“…Clutter effect can be removed by using the singular value decomposition algorithm (SVD) [158]. In [159], the ensemble empirical decomposition (EEMD) and continuous wavelet transform (CWT) were used in a UWB radar to improve the signal-to-noise (SNR) ratio and separate the respiration and heartbeat signals. A low complexity approximation employing the maximum likelihood (ML) estimation of the period of the signal mixed with additive white Gaussian noise (AWGN) was proposed and tested in [160].…”
Section: Algorithms and Signal Processingmentioning
confidence: 99%
“…Clutter effect can be removed by using the singular value decomposition algorithm (SVD) [158]. In [159], the ensemble empirical decomposition (EEMD) and continuous wavelet transform (CWT) were used in a UWB radar to improve the signal-to-noise (SNR) ratio and separate the respiration and heartbeat signals. A low complexity approximation employing the maximum likelihood (ML) estimation of the period of the signal mixed with additive white Gaussian noise (AWGN) was proposed and tested in [160].…”
Section: Algorithms and Signal Processingmentioning
confidence: 99%
“…Recently, Hu and Jin investigated the UWB-IR radar in detecting HR and RR, by using ensemble empirical mode decomposition (EEMD) and continuous-wavelet transform (CWT) [ 70 ]. After a clutter removal stage, EEMD was used to decompose the signal into its intrinsic mode functions (IMFs), thus obtaining a noise reduction effect.…”
Section: Related Workmentioning
confidence: 99%
“…To avoid the codomain restriction in arctangent demodulation (AD), an extended differentiate and cross-multiply (DACM) method was proposed in [21]. Existing vital sign detection techniques are not suitable for trapped victims because they consider only some of the issues, such as removing clutter, determining respiration characteristics, and heart rate estimation [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]. An algorithm for vital sign detection based on radar data was developed in [16].…”
Section: Introductionmentioning
confidence: 99%
“…Further, it was shown that this approach can be used for vital sign detection in other types of noise. Ensemble empirical mode decomposition was used in [38] for heart rate detection.…”
Section: Introductionmentioning
confidence: 99%